Worse sleep architecture but not worse subjective sleep quality is associated with higher cortisol levels in menopausal women - Sahola, Nima (My University, 2023)
It is well known that during and after menopausal transition, women experience worsened sleep, partly caused by the changes in hormonal changes. However, the mechanisms behind this are still not understood well to some extent. The aim of this study is to investigate the connections between plasma cortisol levels and sleep. The subjects were thirty-five women aged from 45 to 71 who were recruited for a three-night sleep study. The women were grouped into perimenopausal (aged 45–51) and postmenopausal (aged 58–71) groups. All night polysomnography was recorded during all 3 nights. The polysomnographs were scored visually. On the fourth evening blood sampling started and samples were taken every 20 minutes. Additional data such as depressive symptoms was collected via questionnaire. Depressive symptoms were evaluated using Beck Depression Inventory (BDI) and Basic Nordic Sleep Questionnaire was used to evaluate subjective sleep. Correlation and regression analyses were performed to evaluate the connections between sleep and plasma cortisol levels. BDI, BMI, and age were used as control variables. In the correlation analysis decreased sleep efficiency, higher wake after sleep onset (WASO)%, stage 1 (N1) sleep %, slow wave sleep (SWS)%, number of SWS periods, SWS latency and number of REM periods were significantly associated with cortisol. SWS latency and SWS% also correlated with faster decrease of daytime cortisol levels. In the adjusted regression analysis lower sleep efficiency, WASO% and number of REM periods had connections with higher cortisol levels. Longer SWS latency and lower SWS% had connections only with higher cortisol awakening response. In conclusion, worse objective sleep in perimenopausal and postmenopausal women was associated with higher cortisol levels.